OPTIMALISASI PERAN KOMUNITAS INTELIJEN DAERAH (KOMINDA) DALAM MENDUKUNG PEMERINTAH DAERAH MEMBANGUN KETAHANAN WILAYAH (Studi Di Kominda Kabupaten Demak Propinsi Jawa Tengah) - Andi Akbar (Universitas Gadjah Mada, 2013)
This paper explained Kominda’s role its strategic value for the regional government to detected each potency, indication and event which would become regional threats and therefore the anticipation steps still be taken to eliminated its development. Kominda activities in performing it’s role due to its intelligence function consist of investigating, securing, and establishing. The qualitative data showed the Kominda’s obstacles were human resources, facilities and infrastructures, coordination and communication, and also budget.Keywords: Regional Intelligence Community, Regional Government, and Regional Resilience.